In vitro effect of Allopurinol on sickling rate and uric acid level in sickle cell erythrocyte. - Nnodim, Johnkennedy (Asian Journal of Medical Sciences, 2013)
Objective: Allopurinol is a drug used for the prevention of gout. The in vitro effect of allopurinol on human plasma and erythrocyte of sickle cell haemoglobin(HbSS) were investigated on uric acid level and sickling rate respectively. Methods: The determination was carried out on samples from 9-25years attending General Hospital Owerri. The plasma uric acid level and sickling rate were determined prior to and after incubation with 100mg standard dose of allopurinol. Results: The plasma uric acid level was significantly decreased (p<0.05) when compared with the control while sickling rate was significantly increased when compared with the control (p <0.05).The results obtained demonstrated that allopurinol could hasten sickling rate and decrease uric acid level. Conclusion: These observations suggest that allopurinol concentration in the circulation might induce marked increased in erythrocyte sickling in vivo and reduced the antioxidant ability of uric acid level in sickle cell disease. Consequently, slow recovery from a sickling crisis. This may be detrimental in the management of sickle cell disease DOI: http://dx.doi.org/10.3126/ajms.v4i3.7992 Asian Journal of Medical Sciences 4(2013) 5-7